Conceptualization and preliminary analysis of a novel reversible photovoltaic window. (15th December 2021) - Su, Xiaosong; Zhang, Ling; Luo, Yongqiang; Liu, Zhongbing; Yang, Huixian; Wang, Xuchao
Highlights: A novel reversible photovoltaic window (RPVW) was proposed for the first time. A numerical model of the RPVW was developed and validated. The impact of key factors on the RPVW was revealed by parameter analysis. The RPVW can achieve 39.78 kWh·m −2 lower electricity consumption than a common one. Abstract: Photovoltaic (PV) windows are promising to reduce building net energy usage by power generation, cooling and lighting loads reduction. However, their shading effect usually leads to the rise of heating loads. A novel reversible PV window was proposed, which shared the same performance of a common one in summer but improved the solar energy utilization efficiency in winter by rotating the PV glazing into the room and reducing the heat lost to the environment. A numerical model of the proposed PV window was developed and validated with experimental data. By using the model, the thermal and electrical performance of the proposed PV window was investigated in the heating periods of Beijing and the influence of key factors on it was revealed. In comparison with a common double-glazed PV window, though the proposed one generated less electric power, its benefits from heating loads reduction outperformed the power reduction. In winter, its net electricity saving increased with the decrease of PV transparency and with the increase of glazing transmittance, and it could be 1.42–10.78, 15.67–34.57 and 18.81–39.78 kWh·m −2 lower than the reference one in naturally ventilated, non-ventilated and auto modes, respectively.